2013
DOI: 10.4161/org.26766
|View full text |Cite
|
Sign up to set email alerts
|

Wnt and planar cell polarity signaling in cystic renal disease

Abstract: Cystic kidney diseases can cause end stage renal disease, affecting millions of individuals worldwide. They may arise early or later in life, are characterized by a spectrum of symptoms and can be caused by diverse genetic defects. The primary cilium, a microtubule-based organelle that can serve as a signaling antenna, has been demonstrated to have a significant role in ensuring correct kidney development and function. In the kidney, one of the signaling pathways that requires the cilium for normal development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 102 publications
1
48
0
1
Order By: Relevance
“…One possibility is that, during kidney development, Wnt5 and Wnt11 participate in both Wnt/ -catenin and PCP signaling. Indeed several Wnt molecules, including Wnt5a, were reported to act in both Wnt pathways [114] but the particular Wnt pathway activation seems to depend on unknown tissue-specific factors [115]. Another possibility is that the activities of the canonical Wnt and the PCP pathways are interdependent.…”
Section: Planar Cell Polarity Pathway and Kidneymentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is that, during kidney development, Wnt5 and Wnt11 participate in both Wnt/ -catenin and PCP signaling. Indeed several Wnt molecules, including Wnt5a, were reported to act in both Wnt pathways [114] but the particular Wnt pathway activation seems to depend on unknown tissue-specific factors [115]. Another possibility is that the activities of the canonical Wnt and the PCP pathways are interdependent.…”
Section: Planar Cell Polarity Pathway and Kidneymentioning
confidence: 99%
“…This important work confirmed that the loss of OCD may contribute to cystogenesis. In subsequent years, numerous studies have examined the complex relationship between the PCP pathway, OCD, and cystogenesis [115,131,132].…”
Section: Advances In Nephrologymentioning
confidence: 99%
“…У Wnt-/PCP-шляху (справа) зв'язування Wnt-ліганду веде до активації Frizzled або Dishevelled з подальшою реорганізацією цитоскелету або ак-тивацією транскрипції через RhoA або Rac1. Ко-рові молекули (Vangl, Celsr, Scribble) важливі для Wnt-/PCP-сигнального шляху, тоді як ефекторні мо-лекули (Fuzzy, Fat4, Ptk7) -для нефрогенезу [7].…”
Section: Wnt-/β-êàòåí³í-ñèãíàëüíèé øëÿõunclassified
“…Disturbances in PCP signaling produce developmental anomalies in neural tube closure, left-right asymmetry, and hair cell orientation in the inner ear (14)(15)(16)(17)(18)(19)(20). In humans, mutations or polymorphisms of PCP components are associated with an array of developmental defects including spina bifida, cardiac outflow malformations, and cystic renal disease (21)(22)(23)(24).…”
Section: Significancementioning
confidence: 99%